Threats to Biodiversity Hotspots: A Case Study of the Wallacea Region, Indonesia - Haliza Tirta, Keny; Wizali, Gesti Defani; Sigit, Diana Vivanti (Indonesian Journal of Ecology and Conservation, 2026)
Indonesia is a megadiverse country, with the Wallacea region among the world's biodiversity centers. Its geographic conditions and geological history create a complex ecosystem that supports a variety of species found nowhere else. However, habitats in Wallacea face major threats from human activities, including deforestation, land conversion, mining, and the introduction of invasive species that can disrupt local ecosystem balance. This research is a literature review that employs a systematic review methodology. Therefore, it is important to study in greater depth the threats facing the Wallacea region as a biodiversity hotspot. Sustainable management of natural resources, strict law enforcement, and increasing public awareness about the importance of maintaining biodiversity are the keys to preserving the Wallacea region